Research on the strength retrogression and mechanism of oil well cement at high temperature (240 ℃). (11th January 2023) - Zhang, Yaxiong; Wang, Chengwen; Chen, Zehua; Yu, Yongjin; Jing, Jianzhou; Xia, Xiujian; Liu, Huiting; Meng, Renzhou
Highlights: Determining the strength retrogression for oil well cement with addition of silica sand under high temperature (240 ℃). Revealing the composition and microstructure changes pattern of oil well cement hydration products at high temperature (240 ℃). Clarifying the evolutionary mechanism of mechanical properties for cement under high temperature and high pressure (240 ℃). Abstract: In light of the problem that the strength retrogression pattern and mechanism of oil well cement containing silica sand at high temperature are still unclear, the strength, permeability, hydration products, and micromorphology for cement containing silica sand under the condition of 240℃ were investigated. The results show that the strength of cement with addition of 50% silica sand gradually decreases with curing time, while the corresponding permeability begins to grow progressively at 240℃. The hydration products are mainly composed of xonotlite and massive scawtite crystals in the early stage. In the later stage, it is needle-rod-shaped xonotlite and scawtite in the surrounding. As a result, the mechanical properties decline significantly. The overall strength of the cement with addition of 80% silica sand is lower than that with 50%, while there are a large number of knitted/coarse needle-shaped crystalline xonotlite and blocky scawtite in the hydration product. Also, xonotlite increases significantly in the early and late stages, but its overall content (for 80% silica sand) was less than the content with additon of 50% silica sand in the same period. This indicates that simply increasing the amount of silica sand could not solve the problem of strength retrogression of cement under extremely-high temperature. The reason for the decline may be that the large content of silica sand inhibits the hydration reaction to some extent.